PELAKSANAAN RELOKASI PEDAGANG JALAN M. HUSNI THAMRIN KE PASAR KELAKAP TUJUH DI KOTA DUMAI TAHUN 2017 – 2018 - Marmi Rosita Dewi; Rury Febrina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The implementation of the relocation of M. Husni Thamrin street traders to the Kelakap Tujuh market in Dumai City in 2017 - 2018 is a step or effort of the Dumai City government to alleviate the problem of M. Husni Thamrin street traders who established 2 traditional markets in an area that is not intended as a trading area. However, the implementation of the policy was not successful in alleviating the problem, this was marked by the return of traders to the M. Husni Thamrin street after relocation was less than 1 month relocated, while the implementation of the relocation had involved many government agencies in the City of Dumai. So the problem raised was regarding "The Implementation of M. Husni Thamrin Street Traders Relocation to the Seven-Day Market in Dumai City 2017 - 2018".This research uses a qualitative approach with descriptive research type. This research is based on Van Meter and Carel Van Horn theory, according to which there are several variables that can affect performance in achieving the objectives of the implementation of Public Policy, namely, Standards and Policy Targets, Resources, Relationships between Organizations, Characteristics of Implementing Agencies, Social Conditions, Politics And Economics, and Implementer Disposition.The results of this study are things that affect the implementation of the relocation of M. Husni Thamrin street traders to the Kelakap Tujuh market in Dumai City in 2017 - 2018 including; the absence of a procedure or criteria that become a benchmark in the implementation of the relocation of the trader so that it is only based on the joint decision of the relocation Integrated Team. Then from the budget resources are quite limited because the budgeting is done after relocation. Moreover, the communication that took place in the implementation of the relocation still had no internal decision regarding the procurement of public transportation and the making of the Kelakap Tujuh market access road, as well as external communication to fish and vegetable unloading traders. plus 2 institutions that play an important role, namely the Market Management Department of the Trade Office, have not been able to add infrastructure to support the Kelakap Tujuh market and from the Satpol PP that have not been able to carry out routine control. In addition, social, political and economic conditions also influence.Keywords: Policy, Implementation, Relocation